PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, PERTUMBUHAN AKTIVA DAN LIKUIDITAS TERHADAP STRUKTUR MODAL (Survei pada Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia 2016 – 2018) - Riski Widityas Ratih; Suprihatmi Sri Wardiningsih; Setyaningsih Sri Utami (Universitas Slamet Riyadi, 2020)
This research was conducted with the aim to examine the effect of company size, profitability, asset growth and liquidity on the capital structure of food and beverage companies listed on the Indonesia Stock Exchange in 2016 – 2018. This study uses a population of 20 food and beverage companies listed on the Indonesia Stock Exchange in 2016 - 2018. The sample in this study amounted to 13 companies with a purposive sampling technique. Data analysis techniques used in this study are the classic assumption test, multiple linear regression analysis and hypothesis testing. The results showed that partially company size and profitability had a significant effect on capital structure, while asset growth and liquidity had no significant effect on capital structure. Simultaneously company size, profitability, asset growth and liquidity have a significant influence on capital structure.